One-loop corrections to the two-body decays of the charged Higgs bosons in the real and complex NMSSM - Thi Nhung Dao; Margarete Mühlleitner; Shruti Patel; Kodai Sakurai (European Physical Journal C: Particles and Fields, 2021)
Abstract We evaluate the full next-to-leading order supersymmetric (SUSY) electroweak and SUSY-QCD corrections to the on-shell two-body decays of the charged Higgs bosons in the framework of the next-to-minimal supersymmetric extension of the Standard Model (NMSSM) allowing also for CP violation. We furthermore provide the possibility to choose between different renormalization schemes in the electroweakino and the squark and slepton sectors. Our corrections are implemented in the code NMSSMCALCEW and thus complete the one-loop corrections of the charged Higgs boson decays which so far only included the state-of-the-art QCD corrections and the resummed SUSY-electroweak and SUSY-QCD corrections. We investigate the impact of the NLO corrections including the newly computed higher-order corrections for each decay mode in a wide range of the parameter space that is allowed by the theoretical and experimental constraints as well as the effect of CP violation and the dependence on the choice of the renormalization scheme. The new version of NMSSMCALCEW is made publicly available.